PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP KINERJA USAHA MIKRO KECIL MENENGAH (UMKM) PADA UMKM DI KECAMATAN CAKRANEGARA - Rizka Ajiutami; Armiani Armiani; Anna Apriana Hidayanti (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the influence of internal factors and external factors on the performance of UMKM in UMKM in Cakranegara District. The variables of this study consisted of 2 independent variables, namely internal factors (X1), external factors (X2), and the dependent variable, namely the performance of SMEs (Y). Samples were taken using stratified sampling (layered sampling) as many as 65 UMKM. The data was obtained by distributing questionnaires to UMKM in Cakranegara District. Questionnaires that return and can be used as many as 65 questionnaires. Data were analyzed using SPSS 16 with Multiple Linear Regression. The results of this study indicate that internal factors affect the performance of UMKM. On the other hand, external factors do not affect the performance of UMKM. Internal factors and external factors together affect the performance of UMKM. These results also show that the dependent variable (business performance) is influenced by the independent variables, namely internal factors (human resources, financial aspects, markets and marketing), external factors (government policies, related institutions, technology) by 34.9%